A peculiar stable region around Pluto - Giuliatti Winter, S. M. [UNESP]; Winter, O. C. [UNESP]; Vieira Neto, E. [UNESP]; Sfair, R. [UNESP] (Oxford University Press, 2014)
Giuliatti Winter et al. found several stable regions for a sample of test particles located between the orbits of Pluto and Charon. One peculiar stable region in the space of the initial orbital elements is located at a = (0.5d, 0.7d) and e = (0.2, 0.9), where a and e are the initial semimajor axis and eccentricity of the particles, respectively, and d is the Pluto-Charon distance. This peculiar region (hereafter called the sailboat region) is associated with a family of periodic orbits derived from the planar, circular, restricted three-body problem (Pluto-Charon-particle). In this work, we study the origin of this stable region by analysing the evolution of such family of periodic orbits. We show that they are not in resonances with Charon. The period of the periodic orbit varies along the family, decreasing with the increase of the Jacobi constant. We also explore the extent of the sailboat region by adopting different initial values of the orbital inclination (I) and argument of the pericentre (omega) of the particles. The sailboat region is present for I = [0 degrees, 90 degrees] and for two intervals of omega, omega = [-10 degrees, 10 degrees] and (160 degrees, 200 degrees). A crude estimative of the size of the hypothetical bodies located at the sailboat region can be derived by computing the tidal damping in their eccentricities. If we neglect the orbital evolution of Pluto and Charon, the time-scale for circularization of their orbits is longer than the age of the Solar system for bodies smaller than 500 m in radius.
Keywords: celestial mechanics; minor planets, asteroids: general